Tardigrades from northwestern Patagonia (Neuquén Province, Argentina) with the description of three new species - Rossi, Gustavo Carlos (2009)
Fifteen moss and lichen samples collected in localities of the Neuquén province, Argentina contained tardigrades and their eggs. Eighteen species were found, three being new to science: Macrobiotus neuquensis sp. nov., Macrobiotus tehuelchensis sp. nov., and Minibiotus claxtonae sp. nov. Macrobiotus neuquensis sp. nov can be differentiated from the other species of harmsworthi group by the presence of a cuticular bar and a refractile zone in the first three pairs of legs. Also the characteristics of the eggs such as the shape and distribution of processes allow a distinction from other species. Macrobiotus tehuelchensis sp. nov. differs from other similar species by the measurements of some structures of the buccal apparatus and the characteristics of the eggs (the shape of the processes). Minibiotus claxtonae is characterized by the presence of three macroplacoids, microplacoid and cuticular pores arranged in transverse bands. The new species of Minibiotus is distinguished from other species of the genus by the distribution and shape of the pores (round and star shaped), presence of granulation on the legs and some characteristics of the eggs (e. g., the absence of a membrane, the shape of the processes).